INTEGRATING SOCIAL MEDIA INTO LANGUAGE LEARNING: THREADS AS A TOOL FOR TEACHING RECOUNT TEXT WRITING - Mutiara Risqi Octaviani; Inayatul Ulya (Universitas PGRI Palembang, 2025)
This research explores the integration of Threads, a text-centric social media application developed by Meta, as an instructional tool for teaching recount text writing. The study was conducted among tenth-grade students at SMK Muhammadiyah Karanganyar, with a central focus on learners’ perceptions regarding the platform’s use in the writing classroom. Employing a descriptive qualitative approach, data were gathered through questionnaires and semi-structured interviews, and subsequently analyzed using Miles and Huberman’s interactive model, which encompasses data reduction, data display, and conclusion drawing. The results reveal that Threads was positively embraced by students. They exhibited not only a solid grasp of the platform’s functionalities but also demonstrated the ability to construct recount texts in a well-organized manner. Students used the reply feature to compose each section sequentially, allowing for logical idea progression and the maintenance of chronological coherence—key characteristics of the recount genre, which includes orientation, series of events, and reorientation. Furthermore, the platform fostered collaborative interaction among peers and stimulated narrative development through its threaded conversation format. Overall, the study concludes that Threads offers a dynamic and supportive digital space for recount writing, significantly enhancing student engagement, narrative coherence, and creative expression.